Experimental study on the thermal-hydraulic performance of a fluttering split flag in a channel flow. (January 2022) - Zhong, X.L.; Fu, S.C.; Chan, K.C.; Yang, G.; Qiu, H.H.; Chao, Christopher Y.H.
Highlights: Inserting a fluttering flag into a channel enhances its heat dissipation. Heat dissipation effect by a split flag is superior to that by a full flag. Hydraulic loss of a split flag is lower than that of a full flag. A split flag starts flutter at a lower wind speed than a full flag. The fluid-structure interaction of a split flag is stronger than that of a full flag. Abstract: The use of flags as vortex generators inside heat sinks has been successfully demonstrated as a heat transfer enhancement technique. However, their thermal-hydraulic performance is usually diminished by the blocking effect induced by the fluttering phenomenon. To tackle this problem, with the expectation to maximize the fluid mixing while minimizing the pressure drop, we report a simple and direct design by splitting a flag into multiple strips. Flags with different strip widths were compared with a full flag on the performance of pressure drop and heat transfer. A high-speed camera is used to investigate their fluttering motion. A piezoelectric plate is attached to the wall to measure the flag's flutter frequency. The results show that the performance of a flag with multiple strips outperforms that of the full flag for its lower pressure drop and higher heat dissipation effect. The performance of split flag is not linear with the strip number and the optimal way in our study is to split the full flag into 4 strips. The maximum thermal-hydraulic performance factor of the split flag is 1.91, which is 26% higher than that of the full flag. Besides, the split flag starts fluttering at a lower wind velocity. All these results demonstrate that the split strategy of a flag acting as a vortex generator is of great potential for improving the heat sink performance.